(untitled) (Diametros, 2005)
The authors emphasize the difference between philosophic knowledge and the formation of an image of the world on the basis of knowledge having its source in the contemporary mass media. Employing, among other things, the concepts of homo videns, and the empty ego, they underline the negative aspects of the personality of a person formed by the mass media. They emphasize the role of philosophy as a traditional antidote to the danger that appears.